Treading Lightly on the Climate in a Problem-Ridden World. Issue 2 (3rd May 2016) - Shahar, Dan C.
ABSTRACT: Personal carbon footprints have become a subject of major concern among those who worry about global climate change. Conventional wisdom holds that individuals have a duty to reduce their impacts on the climate system by restricting their carbon footprints. However, I defend a new argument for thinking that this conventional wisdom is mistaken. Individuals, I argue, have a duty to take actions to combat the world's problems. But since climate change is only one of a nearly endless list of such problems, individuals' obligations to take action as activists do not specifically require reductions in personal carbon footprints. Moreover, this is true even in spite of the fact that we are personally implicated in causing climate change. This paper also argues that many of those who decide to combat climate change by reducing their carbon footprints are likely doing more than they can justify in this regard. Although most people are not doing enough to combat world problems, a proper devotion to activism would seek a balance with other life demands that many climate activists currently eschew.